Systematic Identification of Anti-Fungal Drug Targets by a Metabolic Network Approach - Kaltdorf, Martin; Srivastava, Mugdha; Gupta, Shishir K.; Liang, Chunguang; Binder, Jasmin; Dietl, Anna-Maria; Meir, Zohar; Haas, Hubertus; Osherov, Nir; Krappmann, Sven; Dandekar, Thomas (Frontiers in Molecular Biosciences, 2016)
New antimycotic drugs are challenging to find, as potential target proteins may have close human orthologs. We focus here on metabolic targets as they are critical for fungal growth. We furthermore minimize the similarity of potential targets to human proteins. We compare and combine here: (I) direct metabolic network modeling using elementary mode analysis and flux estimates approximations using expression data, (II) targeting metabolic genes by transcriptome analysis of condition-specific highly expressed enzymes and (III) analysis of enzyme structure, enzyme interconnectedness (“hubs”) and identification of pathogen-specific enzymes using orthology relations. We have identified 64 targets including metabolic enzymes involved in vitamin synthesis, lipid and amino acid biosynthesis including 18 targets validated from the literature, two validated and five currently examined in own genetic experiments, and 38 further promising novel target proteins which are non orthologous to human proteins, involved in metabolism and are highly ranked drug targets from these pipelines.